THE ANALYSIS OF FLOUTING OF CONVERSATIONAL MAXIMS ON THE MAIN CHARACTERS IN “ MOANA” MOVIE - Dini Nurfarwati; Siti Nur Anisa; Rasi Yugafiati (IKIP Siliwangi, 2018)
This study focuses to analise the flouting of conversational maxims which are found in Moana movie. The study uses mix method. There are four of maxims can be revealed. The first is maxim relevance. The reasons of maxim relevance are:“The Maui’s responses do not appropriate to Moana’s statements” and “Moana’s response does not appropriate to Maui’s statement”. The second is maxim manner.The reason of maxim manner are: “Moana’s statements do not clear”, “Maui’s response does not appropriate to Moana’s statement”, and “Maui’s statement does not clear”. The third is maxim quantity. The reasons of maxim quantity are: